1991
DOI: 10.1136/gut.32.9.973
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter pylori infection of the gastric mucosa by measurement of gastric aspirate ammonium and urea concentrations.

Abstract: Helicobacter pylori possesses unusually high urease activity that lowers the urea concentration and raises the ammonium concentration of the gastric juice in infected people. The value of measuring urea and ammonium concentrations in gastric juice obtained during upper gastrointestinal endoscopy as a means of diagnosing the presence and eradication of the infection was assessed. Twenty four subjects with the infection and 14 in whom it had been eradicated were examined. Their Hpylori status was confirmed by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 7 publications
2
20
1
Order By: Relevance
“…In this study, the authors reported a strong correlation between the presence of the bacterium and the levels of ammonium. Subsequently, several other reports have been published on this topic [9,10,11,12,13,14,15,16,17,18]. Most of them confirmed the relation between ammonium and infection but they significantly differed about the concentrations detected (table 2); moreover, an evident overlap between infected and uninfected patients occurred in all studies.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In this study, the authors reported a strong correlation between the presence of the bacterium and the levels of ammonium. Subsequently, several other reports have been published on this topic [9,10,11,12,13,14,15,16,17,18]. Most of them confirmed the relation between ammonium and infection but they significantly differed about the concentrations detected (table 2); moreover, an evident overlap between infected and uninfected patients occurred in all studies.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, the peculiar characteristic of gastric juice makes this determination much more problematic than in other mediums. This may account for the discrepancies reported in the literature about this parameter and its possible role in diagnosing H. pylori infection [8,9,10,11,12,13,14,15,16,17,18]. …”
Section: Introductioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Neithercut et al (12) reported that the median ammonia concentration in gastric juice of H. pylori-infected subjects was 3.4 mM (range, 1.0 to 13.0 mM), which was higher than that in uninfected subjects (0.64 mM [range, 0.02 to 1.4 mM]). In the present study, 2 to 4 mM exogenously added ammonia raised the frequency of apoptosis from around 3% at background to 10 to 40%, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2831 Thus, concentration of ammonia in exhaled breath of human who is infected by Helicobacter pylori is elevated after administration of urea compared with before. 5,31 In this study, the determination of ammonia in the exhaled breath of urease administrated gerbils before and after ingesting urea was carried out to examine whether the elevation of ammonia in exhaled breath was monitored by the present FIA-ECD system As shown in Fig. 6A, the ammonia concentration in the exhaled breath of urease administrated gerbils after urea administration was elevated in comparison with that in the exhaled breath of the negative control gerbils and urease administrated gerbils before urea administration.…”
Section: Determination Of Ammonia In Human Exhaled Breathmentioning
confidence: 99%